Fiscal Subordination and Proposal Driven Dependency in West Sumatra’s Local Budget - Rozidateno Putri Hanida; Redni Putri Meldianto (Policy & Governance Review, 2026)
Fiscal decentralization has been undertaken to strengthen the fiscal autonomy of SNG and to enable them to monitor the achievement of local development priorities and public service delivery functions. Regional budget formation and bargaining may be affected in the long run by efficiency oriented fiscal transfer mechanisms and new institutional setups. Considering the allocation of fiscal transfers based on efficiency‚ this paper uses a qualitative case study approach to identify three issues: how sectoral fiscal transfers are allocated‚ how institutional mechanisms are used to access them‚ and how sectoral fiscal transfers are integrated into the budget process at the provin cial level in West Sumatra. Field data was collected from a document analysis of fiscal transfer allocations and provincial budget planning documents‚ and semi structured interviews with government officials involved in budgeting and development plan ning processes. The findings revealed two dynamics. First‚ efficiency oriented fiscal transfer mechanisms reinforce structural fiscal dependence on centrally administered funding schemes. As a result‚ it is difficult for provincial governments to develop their own development programs‚ especially when the fiscal transfers do not cover minimum needs for a certain level of service. Second‚ the institutional design of pro posal based transfer mechanisms shifts the locus of determination of many program priorities away from political debates in the provincial legislature toward technocratic administrative planning processes in regional governments’ bureaucracies. As a re sult‚ many program priorities are determined at the planning stage before the provin cial budget process‚ and not during it. Thus‚ the study adds to the literature on fiscal decentralization by shifting the attention to fiscal transfer systems‚ which affect both the allocation of financial resources across levels of government and the character of subnational governance. It shows that fiscal transfer systems also effectively shape regional fiscal autonomy and the budget deliberation process. Based on the findings‚ it argues for the study of intergovernmental fiscal transfer systems through the lens of regional governance.